POTENSI TANAMAN PANDAN LAUT (Pandanus tectorius) DAN LIMBAH INDUSTRI GANDUM KOTA CILEGON SEBAGAI BAHAN BAKU SINTESIS BIOETANOL - Agus Malik Ibrahim; Agrin Febrian Pradana; Gagas Priyosakti; Miftahul Arifin; Tuti Alawiyah; Perliansyah (Jurnal Penelitian Hasil Hutan, 2025)
The minimum requirement of bioethanol utilization (E100) as a mixture of fuel oil is required as much as 20%, of the total needs in January 2025 as stated in the Regulation of the Minister of Energy and Mineral Resources number 12 in 2015. Indonesia is a country that has many potential raw materials for the development of bioethanol as renewable energy, such as sea pandanus plants (Pandanus tectorius) and food industry wastes such as the wheat industry. Sea pandanus plants are commonly found throughout the Indonesian archipelago and are available endemically. While wheat industrial waste is available in industrial areas such as in Banten Province, which has so far not been utilized as a source of biofuels. The purpose of this research is to get bioethanol product from new sources based on natural materials and industrial waste. The stages of research began with raw materials preparation, proximate analysis, gelatinization, liquefaction, pre-saccharification, fermentation, distillation process, and quantitative analysis using instruments. The results showed that the sea pandanus leaf had the potential for bioethanol synthesis with the highest amount of recovery and efficiency were 309 mL and 0.62 mL/g respectively, whereas based on the results of gas chromatography (GC) analysis, the bioethanol product which had the highest purity was from wheat bran waste with a purity level of 97.64%.